1995
DOI: 10.1523/jneurosci.15-02-00990.1995
|View full text |Cite
|
Sign up to set email alerts
|

Soluble factors from the olfactory bulb attract olfactory Schwann cells

Abstract: Olfactory Schwann cells (OSCs) extend processes that ensheathe bundles of olfactory axons as they course from the olfactory epithelium to the olfactory bulb (OB). Results of morphological and immunohistochemical studies have led to speculation that OSCs may be involved in guiding the olfactory axons to their target tissue. In this study we have explored this possibility by investigating the relationship between OSCs and the OB. Olfactory Schwann cells labelled with 1,1′-dioctadecyl 3,3,3′,3′-tetramethylindocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…It has been shown that the OB secretes some soluble factors that might attract OEC migration from the OE towards the OB (Liu et al, 1995). Another potential guidance mechanism for OEC migration is that the OE might secrete some repellants to promote OEC migration toward the OB during early development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the OB secretes some soluble factors that might attract OEC migration from the OE towards the OB (Liu et al, 1995). Another potential guidance mechanism for OEC migration is that the OE might secrete some repellants to promote OEC migration toward the OB during early development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus in doing so, OECs effectively penetrate the transition zone between the periphery and CNS [14,15]. It has been demonstrated that the directional cue for this migration may be due to soluble factors originating from the target tissue, the olfactory bulb [16]. Although the identity of olfactory bulb-derived factors has yet to be identified, a recent study showed that glial cell line-derived neurotrophic factor stimulates intercellular interaction of lamellipodial waves that contribute to OEC migration [17] and which may be critical for the establishment of olfactory axon projections between the nasal cavity and the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that the OB released long-range attractants, which may act in concert with permissive OEC cues. These bulb-derived attractants may be identical to the ones that attract OECs in early development (Liu et al, 1995), although it has to be kept in mind that substances may diffuse over longer distances in the culture dish than they might do in the tissue in vivo. Closer investigation of factors released by the precultured bulb and their potency to attract axons are now feasible, and their effect on the growth cone can be tested in live imaging experiments.…”
Section: Discussionmentioning
confidence: 99%